Pricing barrier options when the dynamics of the prices are driven by the mean reverting process - Komunte, Masoud (University of Dar es Salaam, 2023)
A dissertation submitted in partial fulfillment of the requirements for the Degree of Master of Science (Mathematical Modelling) of the University of Dar es Salaam